Perikymata number and spacing on early modern human teeth: evidence from Qafzeh cave, Israel - Janet M. Monge; Anne-Marie Tillier; Alan Mann (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The microscopic anatomy of dental enamel has been employed in numerous studies of fossil hominin teeth. This research has focused on the use of microstructure, primarily perikymata and, when available, their internal manifestations, in the construction of phylogenetic relationships as well as in the reconstruction of hominin patterns of growth and development. The literature on perikymata numbers and packing as reported over the last 20 years, shows a huge range of variation within modern humans. The variation is so large in fact that virtually every fossil hominin species can be encompassed within the range except for some but not most of the robust australopithecines. The sample of Mousterian level hominins from the site of Qafzeh, in northern Israel represents some of the earliest recognized members of Homo sapiens sapiens. Included in this sample are a number of immature individuals (N = 5) whose permanent incisor crowns have observable perikymata. The number of perikymata on complete and unworn teeth is within the range of variation of other hominins and does not provide specific evidence for attributing these specimens to one hominin taxon or another. Similarly, the pattern of perikymata compaction toward the cemento-enamel junction of the Qafzeh specimens is compared to published sources.